We Have Always Been Transcultural: The Arts as an Example - Welsch, Wolfgang, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2024., 2024)
Wolfgang Welsch demonstrates for the first time that transculturality - the mixed constitution of cultures - is by no means only a characteristic of the present, but has de facto determined the composition of cultures since time immemorial. The historical transculturality is demonstrated using examples from the arts. While transculturality was often viewed with reservation where political, social, or psychological levels were at stake, it was rather welcomed and appreciated in the field of art. The book therefore demonstrates the historical prevalence of transculturality via all areas of art and does so with respect to all cultures and continents of our world.